2017
DOI: 10.1080/15569527.2017.1315128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects on choroidal thickness of bimatoprost 0.03% versus a brinzolamide 1.0%/timolol maleate 0.5% fixed combination

Abstract: The use of topical ocular hypotensive medication in eyes with OAG results in an increase in CT. This increase is relatively greater with bimatoprost 0.03% therapy compared to BTFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Majority of our cases, that is, 23 out of 25 eyes (92%), were on prostaglandin analogues, which could have contributed to increased CT. This is supported by a study done by Akyol et al 15 who looked at the SFCT using Optovue RTVue. In patients newly diagnosed with glaucoma, CT was compared before and after starting treatment on bimatoprost in one group and brinzolamide with timolol in another group.…”
Section: Discussionsupporting
confidence: 65%
“…Majority of our cases, that is, 23 out of 25 eyes (92%), were on prostaglandin analogues, which could have contributed to increased CT. This is supported by a study done by Akyol et al 15 who looked at the SFCT using Optovue RTVue. In patients newly diagnosed with glaucoma, CT was compared before and after starting treatment on bimatoprost in one group and brinzolamide with timolol in another group.…”
Section: Discussionsupporting
confidence: 65%
“…Ancak, literatürde antiglokomatöz ajanlarının KK'yı etkilediğini gösteren çalışmaların yanında, anlamlı etki göstermeyen araştırmalar da mevcut olup konu tartışmalıdır. [22][23][24] SONUÇ RSLK incelmesi, PES'li hastalarda glokom gelişimi açısından önemli bir erken tanı bulgusu olabil-mektedir. Ayrıca, PES'li gözlerde RSLK değerlendirmelerinde glokom açısından anlamlı değişiklik saptanmaz iken, KK'de incelme bulunması; RSLK değişimlerinden daha önce saptanan bir bulgu olarak uyarıcı değer taşıyabilmektedir.…”
Section: Discussionunclassified
“…It is worth noting that lowering the IOP can promote ChBP. For example, topical ocular hypotensive drugs such as bimatoprost and dorzolamide have been shown to increase ChBP and cause a marked increase in CT. 69 , 70 For every 1-mm Hg decrease in IOP after trabeculectomy, the mean increase in CT was 3.4 µm, and these postoperative changes were maintained for at least 6 months. 47 , 71 Interestingly, several interventions to retard myopia progression in children and teenagers, such as orthokeratology treatment and low-dose atropine, also increased ChBP or CT. 72 , 73 This suggested that increasing ChBP may be a significant target in high myopia control.…”
Section: Choroidal Response To Iopmentioning
confidence: 94%